Isotopic Determination of Serum Vitamin B12 Level using Sephadex G-25 - Mantzos, J.; Gyftaki, H.; Alevizou, V. (Nuklearmedizin - NuclearMedicine, 1967)
A radioisotope method for the determination of the serum vitamin B12 level is described. The method is based on the principle of saturation analysis and on the ability of Sephadex to separate free from bound vitamin.We have found the method to be sensitive, reproducible and fairly rapid. Because of its simplicity, it can be used in any laboratory equipped for the use of radioisotopes.The method was applied to determine the level of Vitamin B12 in 71 normal subjects and in 15 patients with different diseases.